HOTSED: A new integrated model for assessing potential hotspots of sediment sources and related sediment dynamics at watershed scale - Manuel La Licata; Alberto Bosino; Seyed Hamidreza Sadeghi; Mattia De Amicis; Andrea Mandarino; Andrea Terret; Michael Maerker (International Soil and Water Conservation Research)
In this paper we introduce HOTSED, a novel, innovative GIS-based model designed for assessing potential hotspots of sediment dynamics at watershed scale. HOTSED integrates geomorphic spatial information with both structural and functional properties of connectivity. HOTSED provides a single and intuitive output that depicts the location of sediment source hotspots. Moreover, it enables the identification of “relative hazard” classes for sediment production and related effects. The general methodological framework is based on the initial elaboration of an Inventory Map (IM) of sediment-related landforms and processes, along with the implementation of a corresponding database. Subsequently, we used data stored in the IM to estimate the geomorphic Potential of Sediment Sources (PSS) through a relative scoring system. Furthermore, we computed Structural Sediment Connectivity (STC) and the Potential for Sediment Transport (PST) by combining terrain and hydrological parameters, vegetation roughness, and rainfall erosivity. Afterwards, PSS, STC, and PST components are integrated through a raster-based calculation method yielding the HOTSED model. We tested the HOTSED procedure in the upper Val d’Arda-Mignano watershed, which is a representative geomorphologically highly active Mediterranean area of the Northern Apennines (Italy). Through photointerpretation, terrain analysis, and fieldwork, we mapped sediment-related geomorphic features for a total of 4640 ha including: badlands and gullies (0.26%), rill-interrill erosion (15.03%), fluvial erosion (0.03%), landslides (70.06%), litho-structural erosional systems (0.87%), slope deposits (12.56%), and alluvial deposits (1.19%). HOTSED revealed hotspots with a very high hazard potential located near main channels or upstream of the reservoir. These areas are often linked with active landslides highly connected to the drainage system and frequently associated with other processes like bank erosion or surficial soil erosion. The model also highlighted linear hotspots corresponding to drainages flowing alongside or intersecting complex geomorphic systems such as landslides. Furthermore, HOTSED identified areas where sediments are stored in depositional landforms, exhibiting a low hazard potential, considering both low geomorphic potential and sediment connectivity. Our conceptual model is generally applicable but proves to be particularly effective in areas characterized by complex and polygenetic geomorphic systems, such as the Northern Apennines. HOTSED offers a valuable tool for watershed authorities to support sustainable watershed and reservoir management.